2022
DOI: 10.1007/s00464-021-08770-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs. laparoscopic liver surgery: a single-center analysis of 600 consecutive patients in 6 years

Abstract: Background While laparoscopic liver surgery has become a standard procedure, experience with robotic liver surgery is still limited. The aim of this prospective study was to evaluate safety and feasibility of robotic liver surgery and compare outcomes with conventional laparoscopy. Methods We here report the results of a single-center, prospective, post-marketing observational study (DRKS00017229) investigating the safety and feasibility of robotic liver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Major hepatobiliary centers usually started robotic programs after a solid background of laparoscopic liver surgery, and the point of the safety of simultaneous training could not be addressed. For example, D’Hondt and his team from Belgium performed LLRs-only for 8 years before the transition to RLR; similarly, the Berlin experience consisted of at least 7 years of LLRs before starting with RLRs 11 , 28 . The features of a purely robotic learning curve would be interesting but could not be addressed in the present study; however, it could be investigated following the same scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Major hepatobiliary centers usually started robotic programs after a solid background of laparoscopic liver surgery, and the point of the safety of simultaneous training could not be addressed. For example, D’Hondt and his team from Belgium performed LLRs-only for 8 years before the transition to RLR; similarly, the Berlin experience consisted of at least 7 years of LLRs before starting with RLRs 11 , 28 . The features of a purely robotic learning curve would be interesting but could not be addressed in the present study; however, it could be investigated following the same scheme.…”
Section: Discussionmentioning
confidence: 99%
“…similarly, the Berlin experience consisted of at least 7 years of LLRs before starting with RLRs. (11,27) The features of a purely robotic LC would be interesting, but could not be addressed in the present study; however, it could be investigated following the same scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [148] revealed intra-and postoperative outcomes among patients who underwent RALR (n = 71), LLR (n = 141), and OLR (n = 157) for HCC; operation time was shortest and the length of hospital stay was longest in patients who underwent OLR, and similar results were demonstrated between those who did RALR and LLR. Conversely, some studies reported a higher incidence of postoperative bile leakage after RALR [149][150][151]. RALR is easy to manipulate in the hepatic hilum, but the lack of tactile sensation may cause inadvertent bile duct injury.…”
Section: Robot-assisted Liver Resection (Ralr)mentioning
confidence: 99%